Efficacy of selective neurotomy for focal lower limb spasticity: a systematic review - Danique J.M. Ploegmakers; Hanneke J.R. van Duijnhoven; Liron S. Duraku; Erkan Kurt; Alexander C.H. Geurts; Tim de Jong (Medical Journals Sweden, 2024)
Objective: Selective neurotomy has been suggested as a permanent treatment for focal spasticity. A systematic literature review was performed to investigate the efficacy of selective neurotomy regarding focal lower limb spasticity. Methods: A systematic search in PubMed, Medline, Cochrane, and Embase databases was carried out. Studies were included if they reported on the following outcomes: muscle tone, muscle strength, pain, ankle range of motion and/or walking speed, after selective lower limb neurotomy in any type of upper motor neuron syndrome. Results: A total of 25 non-randomized and/or uncontrolled studies and 1 randomized controlled study were selected. The included studies reported improvements in terms of leg muscle tone, pain, passive range of ankle motion, and walking speed. Conclusion: The results suggest that selective neurotomy is effective for reducing lower limb spasticity, without any negative effects on walking speed. However, this conclusion is primarily based on uncontrolled case series, whereas conclusions on clinical efficacy should preferably be based on comparison with a reference treatment through (randomized) controlled trials. Future studies should also include quantitative, validated functional assessment tools to further establish the efficacy of selective neurotomy as long-lasting treatment for patients with focal lower limb spasticity.